Dispatcher-assisted CPR can it do harm as well as good?. (January 2022) - Ferguson, Craig
Abstract: Outcomes for patients with out-of-hospital cardiac arrest can be improved by bystander cardiopulmonary resuscitation (CPR). Dispatcher-assisted CPR increases both the likelihood of CPR being performed, and the chance of survival for the arrested patient. Due to the urgency of the situation, CPR may be advised in patients who are subsequently found not to be in cardiac arrest. Ng and colleagues look at whether bystander CPR causes harm in this group of patients.